Plant cell wall patterning and cell shape - Fukuda, H (Hiroo) (Hoboken, New Jersey : Wiley Blackwell, 2014)
Cell walls are defining feature of plant life. The unique and multi-faceted role they play in plant growth and development has long been of interest to students and researchers. Plant Cell Wall Patterning and Cell Shape>looks at the diverse function of cell walls in plant development, intercellular communication, and defining cell shape. style="font-family: Arial; font-size: 13px;" /> style="font-family: Arial; font-size: 13px;" />Plant Cell Wall Patterning and Cell Shape>is divided into three sections. The first section looks at role cell walls play in defining cell shape. The second section looks more broadly at plant development. While the third and final section looks at new insights into cell wall patterning.
Cytoskeletal Regulation of PC Morphogenesis: Counteraction between ROP-mediated Cortical Actin Microfilament and MicrotubulesSelf-organizing Mechanism Controls the Localized Auxin Transport Critical for PC Morphogenesis; Coordination of Interdigitative Growth by Auxin; Connecting Signals to Rop GTPases: GEFs as Activators of ROP Signaling; Future Perspectives; Acknowledgements; References; Chapter 7: Xylem Cell Wall Pattern Formation Regulated by Microtubule-associated Proteins and ROP GTPases; Introduction; Microtubules and Secondary Wall Development in Xylem Cells
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Plant cell walls; SCIENCE / Life Sciences / Biochemistry; Plant cell walls; Electronic books; Electronic books